Simulation and Experimental Investigation of Pulsed Eddy Current Technique for Defect Evaluation - Nurul A'in Ahmad Latif; Ilham Mukriz Zainal Abidin; Nordin Jamaludin (IAES Indonesian Section, 2018)
Pulsed eddy current (PEC) is an advanced Non-Destructive Testing (NDT) technique that uses transient waveform for their coil excitation. It has the advantage of gathering different depth information in a single excitation process, thus provide the solution towards the drawbacks by both single and multi-frequency eddy current testing. In this work, experimental and simulation investigations on PEC were conducted to establish the correlation between PEC signals and different defect i.e. crack, depths. Initial FEM simulation work has provided understanding of the underlying phenomena of the PEC results through the visualisation of the induced eddy current and defect interaction in the SS 304 sample. Features from the differential magnetic field transient profiles have provided information of the crack in terms of its depth and location. The understanding of the PEC responses and results can be extended for future work in quantitative evaluation of defect in conductive samples by PEC.